Oral health-related quality of life of paediatric patients with AIDS - Goursand Daniela; Andrade Samantha B; Marques Heloísa HS; Domaneschi Carina; Massarente Débora B; Antunes José LF (BMC, 2011)
Abstract Background Children with Acquired Immune Deficiency Syndrome (AIDS) exhibit impaired dental status, which can affect their quality of life. This study assessed the oral health-related quality of life of these patients and associated factors. Methods The "Child Perceptions Questionnaire 11-14", rating overall and domain-specific (oral symptoms, functional limitations, emotional well being, and social well being) oral health-related quality of life (OHR-QoL) was completed by 88 children with AIDS assisted in the Child Institute, Sao Paulo, Brazil. Parents or guardians provided behavioural and socio-demographic information. The clinical status was provided by hospital records. OHR-QoL covariates were assessed by Poisson regression analysis. Results The most affected OHR-QoL subscale concerned oral symptoms, whose rate was 23.9%. The direct answer for oral health and well being made up a rate of 47.7%. Brushing the teeth less than two times a day and viral load exceeding 10,000 HIV-RNA copies per millilitre of plasma were directly associated (p < 0.05) with a poorer oral health-related quality of life. Conclusions Children with more severe AIDS manifestations complained of poorer status of oral symptoms, functional limitations, emotional and social well being related to their oral health. Recognizing the factors that are associated with poorer OHR-QoL in children with AIDS may contribute to the planning of dental services for this population.